Uma análise de ferramentas para auxiliar o gerenciamento ágil de projetos de software - Cavalcante, Weldemio José de Oliveira da Silva (2021)
Due to the significant needs of the job market, the importance of knowing tools that help the improvement of software projects is remarkable. In this context, tools to assist Agile Project Management have been investigated to transform, aid, and improve projects to make them more efficient. Thus, this study aims to carry out a comparative analysis between opensources, freemium and paid with free trial tools for Agile Project Management. In this research, 22 tools were analyzed through 34 guidelines defined from the related works identified, the documentation, and the evaluation of the use of tools.The results achieved indicate that the Asana and Airtable tools covered more than 88% of the guidelines. Therefore, this study presented different characteristics of the tools related to integration, scope, schedule, quality, risks, communication, generation of artifacts and management, to help users choose the tool that best meets their needs.